DORA BRUDER AS AN AUTOBIOGRAPHICAL WRITING OF PATRICK MODIANO - Mira Utami (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2020)
Trauma become a part of memory in human life in regard with past. The form oftrauma as an emotional scar inside an individual can follow the heirs, reflected in the life oflater generations. It also happens in literature, as a way to unconsciously share the traumaticevents, as the result of author memories. Dora Bruder is a novel by Patrick Modiano whichis written as the way to release the experience of diffculties in the past that likely become histrauma. This research will describe the condition of Dora Bruder as an autobiographicalnovel of Modiano because it is happened to share the same difficulties, such as a bad-termrelationship with family and lost family members. The research is based on theory of Memoryby Anne Whitehead and Postmemory by Marianne Hirsch.